Mealworm Powder as Culture Media of Local Isolate Semarang Entomopathogenic Nematodes - Priyantini Widiyaningrum; Minnathul Khasanah; Dyah Rini Indriyanti (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2018)
Many researchers confirmed that entomopathogenic nematodes (EPNs) of the genera Heterorhabditis and Steinernema can be cultivated in vitro using artificial media that containing animal nutrition. However, artificial media with insect component hasn’t been widely studied. This research aims to analyze the population of EPNs isolate of Semarang cultivated in mealworm powder media. Five doses of mealworm powder (Tenebrio molitor) were tested in this research, i.e: 0.5; 1.0; 1.5; 2.0 g. Culture media using 1 g of mealworm larvae was used as control. The best treatment was further tested for its pathogenicity on Macrotermes sp. at seven levels of invective juveniles (IJs) : 0; 50; 100; 150; 200; 250; 300 IJs/mL. Each treatment was repeated five times. The EPNs population and termites mortality were analyzed using ANAVA, whereas pathogenic value was calculated using Probit analysis. The result showed EPNs population were significantly (LSD test; α 0.05), likewise on termites mortality. The EPNs isolate of Semarang optimally at 0.5 g mealworm powder and pathogenicity against termites based on LD50 and LD90 values at 220 JI/mL and 410 JI/mL doses, respectively. In conclusion, this result can be an alternative to mass cultivation of EPNs, in effort of development of local bioinsecticides. The findings of this study also inform farmers that EPNs can be easily cultivated using the simple and available materials.